Academic Writing with IT Researchers: Co-editing as an Instructional Technique - LLANEZA, GABRIELA (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
Globalisation and the World Wide Web have fostered the pervading use of English as a Lingua Franca among international academic contexts. Scientific knowledge exchange, participation in congresses or paper publications require Latin-American researchers, regardless of their field, to effectively command English, without which they can hardly access socialisation, promotion or consistent funding. Nonetheless, postgraduate seminars fail to address this need to write in EFL. In this article I describe the challenges faced by two Computer Sciences researchers for the Argentinian Scientific and Technical Research Council (CONICET) to produce texts for international journals. Then, I include a description of the process of coediting based on the Cognitive Process Theory of Writing and list the IT tools employed to co-edit their work in private classes. Finally, I analyse researches´ perception on the benefits of co-editing.